Countering Patriarchy Hegemony - Kurniawan, Rofii Zuhdi; Jelena Jasmine (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The dominance of male leadership in politics indicates that patriarchal hegemony by the media is deeply entrenched in various layers of society. Women who enter political leadership are considered subordinates of men. Such dominant patriarchal hegemony has undermined and suppressed women’s leadership in the political sphere. This article aims to discuss how Megawati Soekarnoputri in Indonesia and Margaret Thatcher in the United Kingdom emerged against the patriarchal hegemony entrenched in the political systems of their respective countries. We applied a qualitative approach and desk study as a research method, as well as Gramsci’s concept of counter-hegemony. The analysis shows that there were three primary issues that Megawati and Thatcher opposed: (1) dependence on men in building political careers, (2) weak female leadership, and (3) the expectation for women to be obedient. By opposing these issues, these two women leaders could stand out in their respective political arena.